Penser les dieux grecs entre Genève et Paris = Thinking Greek Gods Between Geneva and Paris - Ellinger, Pierre (Mythos, 2025)
Pierre Ellinger looks back at the exploration of the pantheon and the figure of the gods in Ancient Greece, through an overview of some developments concerning the gods, notably Pan, Artemis, Hermes and Apollo, that have resulted from the dialogue between researchers in Geneva and Paris since the seventies of the twentieth century. He illustrates how these exchanges and debates have led to a rethinking of the ‘mode of action’ model to understand what a god is in the Greek polytheistic framework, and looks at the place of his own work within these exchanges.